РІВНІ ІНШОМОВНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНІХ ФАХІВЦІВ СОЦІАЛЬНОЇ СФЕРИ - Павелків К. М. (International Journal of Innovative Technologies in Social Science, 2019)
The article presents the results of experimental research of foreign language competence level of future social sphere specialist. The experimental data are compared with the results of students’ under study self-assessment of their foreign language competence level. The article shows the results of the influence of methodological system of foreign language training of future social sphere specialist on the increase of the level of foreign language competence among participants of experimental groups. Creative, medium, satisfactory and unsatisfactory levels of foreign language competence of future social sphere specialist are characterized from the point of view students’ reflexion. The research approves the effectiveness of pedagogical influences introduced at the forming stage of the experiment through approbation of the author’s methodical system of foreign language training in the university.